Reinforcement Pattern Religion, Social, and Marriage Law for Resistance Family Baha'i Minority in Indonesia - Rusdin Muhalling; Mohd Zaidi Daud (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2023)
The lives of minority groups have slightly different forms of interaction in religious aspects, social relations, and marriage law. Minority groups often experience discrimination in religious, social, and marriage administration services. This research provides an overview of religious patterns, social relations, and marriage law for the Baha'i minority group in Indonesia and the obstacles they face in interacting with general community groups. This research is qualitative research with a phenomenological approach. The participants in this study amounted to 10 people who were heads of families of the Baha'i group. The study's results found four crucial aspects of the life of the Baha'i community. First, the Baha'i group in religious life has three principles: the existence of the One God, the unity of all religions, and human unity. Second, the Baha'i group socially has no problems with the general public and can be socially accepted. Third, the Baha'i group in the legal aspect of marriage cannot access the legal registration of marriage. They perform inter-group marriages only and are only known to their group. Fourth, the obstacles experienced by the Baha'i group are more related to social and state rights services. The results of this study contribute theoretically to enriching and strengthening science and practically will reduce social problems in society, especially respect for minorities such as the Baha'i group.